A critical realist account of a mentoring programme in the Faculty of Pharmacy at Rhodes University - Oltmann, Carmen (Rhodes University, Faculty of Pharmacy, Pharmacy, 2009)
This study originates from experiences I had as supervisor of the mentoring programme for first year students in the Faculty of Pharmacy, at Rhodes University. Our mentoring programme is a strategy for first year students "“ specifically those from previously disadvantaged backgrounds "“ to succeed at Rhodes University. Using an ontological meta-theory - critical realism - as my analytical lens, discourse as my unit of analysis, and Invitational Learning Theory as a theoretical tool I developed a model of mentoring based on Bhaskar's transformational model (1993). This model illustrates the relationship between structure, culture and agency. Whilst developing this model I focussed on determining how mentors construct mentoring, and how mentoring facilitates access to a Community of Practice (CoP). Mentoring involves providing a shared space that is safe, that the mentor and mentee feel comfortable in, and that supports and challenges both the mentor and the mentee. It is a reciprocal, developmental relationship for both the mentor and the mentee that deals with issues that the mentee deems as 'real'. Mentoring is a process, not an outcome. The mentoring strategies that the mentors employed changed as the mentors mentored. Mentors help mentees by using structures and mechanisms that worked for them, and/or by helping mentees access these structures and mechanisms. Mentoring facilitates access to a CoP by providing opportunities for engagement. This involves sharing of experiences and knowledge, and promoting discussion. The mentor helps the mentee move from being a peripheral member of the CoP to becoming a main member, i.e., becoming active, learning with and from others within the CoP. CoPs develop social capital and knowledge management. My research suggests that the knowledge, skills and attitude developed by the mentors within this study may be transferable to other aspects in Pharmacy.
Keywords: Rhodes University -- Academic Development Programme; Pharmacy -- Study and teaching (Higher) -- South Africa; Mentoring in education -- South Africa; Mentoring in Science -- South Africa; Critical realism; Communities of practice